Photoinduced Hydroxylation of Organic Halides under Mild Conditions - Cai, Yue-Ming; Xu, Yu-Ting; Zhang, Xin; Gao, Wen-Xia; Huang, Xiao-Bo; Zhou, Yun-Bing; Liu, Miao-Chang; Wu, Hua-Yue (Organic letters, 2019)
Presented in this paper is photoinduced hydroxylation of organic halides, providing a mild access to a range of functionalized phenols and aliphatic alcohols. These reactions generally proceed under mild reaction conditions with no need for a photocatalyst or a strong base and show a wide substrate scope as well as excellent functional group tolerance. This work highlights the unique role of NaI that allows a challenging transformation to proceed under mild reaction conditions.